Global trends of the digital economy development - Zernova L.E., Kolesnikov A.V.,; Sigidov Yu.I, Degtyareva V.V., Panko Iu.V., (Opción, 2020)
There is still no single harmonized concept of “Digital economy” in the world, and we are talking about digital technologies and their impact on the economies of countries. The aim of this article is to identify global trends in the digital economy development and its tools – digital technologies. In particular, in the developed countries of the world, the culture of using digital technologies is higher, and involves not only the use of postal communication systems, but also banking services, searching for information, etc. While in developing countries, this level of culture is only being formed